Effect of local rhizobacteria isolated from wheat rhizosphere on indole acid and ammonia production and phosphate analysis (Damascus University Journal of agriculture sciences, 2025)
This study aimed to isolate local bacteria from the rhizosphere of some cultivated and wild grassy plants in several regions of Syria and to determine the characteristics of these isolates and How much to which they belong to the group of bacteria that promote plant growth PGPR through their distinction in facilitating phosphates, producing ammonia, or producing indole acetic acid (IAA), where /22/ isolates Local were isolated from /10/ different areas and compared with three isolates in the Bacterial Diseases Laboratory. And the results of/22/ isolates testing showed that only 27.2% of them were phosphorus facilitating, only 22.7% of the isolates produced indole acetic acid IAA, and 40.9% of the isolates were characterized by the production of ammonias.The results of the tests showed that the best isolate was 10.2, and as a result of the biochemical and molecular analysis, it belonges to Serratia liquefaciens.
Keywords: Rhizosphere; Serratia Liquefaciens; Plant Growth-Promoting Bacteria (PGPR)